A method for sintering connection of a laser-processed rough copper surface and nano-copper solder paste
By combining laser processing and plasma cleaning with multiple coatings and high-temperature sintering of nano-copper solder paste, the problem of unreliable bonding on rough copper surfaces is solved, achieving high shear strength and process stability, making it suitable for industrial mass production.
Patent Information
- Application Number
- CN202611490102.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-11-03
AI Technical Summary
In existing technologies, it is difficult to achieve reliable bonding on rough copper surfaces, and defects such as voids and gaps are prone to appear at the interface of sintered bodies. The shear strength is insufficient, and the process stability is poor, making it difficult to adapt to industrial mass production.
A femtosecond laser with a wavelength of 1035nm was used to perform micro-nano processing on the copper surface. Combined with plasma cleaning and multiple coatings of nano copper solder paste and low-temperature drying, a sandwich structure was formed and then sintered at high temperature. The sintering process conditions were optimized.
It improves the shear strength of the copper interface by more than 50%, forms a dense and uniform sintered body, has strong process stability, and is suitable for industrial production.
Smart Images

Figure CN123025006A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electronic packaging and micro-nano interconnect technology, specifically relating to a sintering connection method between a laser-processed rough copper surface and nano-copper solder paste. Background Technology
[0002] Semiconductors, as the cornerstone of the rapid development of the modern information technology industry, are widely used in industries such as smart grids, new energy vehicles, home appliances, the Internet of Things, supercomputers, mobile phones, and 5G. They are of great significance to the realization of a digital and intelligent society and have become one of the important standards for measuring a country's global technological competitiveness and comprehensive national strength. As semiconductor devices continue to develop towards high-density integration, miniaturization, and high performance, they need to operate at higher temperatures. To ensure reliability during operation, many researchers have modified the copper interface to strengthen the sintering bond between the interface and the solder, achieving better interface shear strength and connection performance.
[0003] In existing technologies, nanoscale bump structures are fabricated at the wafer level, and sponge-like Au nanoporous films are prepared on the top of the bumps using chemical etching. These films are then applied to hot-press flip-chip bonding, achieving successful bonding results at 10 MPa and 150 °C. Another existing technology designs an Ag nanostructure deposited using pulsed laser deposition (PLD) and modifies it onto a Cu interface as an intermediate layer. This approach achieves high shear strength with a relatively short time, demonstrating that after surface activation, only a small amount of energy is needed to obtain a reliable interface connection. However, the micro / nano structures generated in these methods are small, requiring only a thin layer of solder to achieve stable connections. When the micro / nano structure size is large and the surface roughness is high, this approach requires further optimization. To address the problem of sintering connections on high-roughness copper surfaces, existing methods suffer from complex processes, poor feasibility, long sintering times, high sintering temperatures, high sintering pressures, and limitations in mass production. Summary of the Invention
[0004] To address the problems existing in the prior art, the present invention aims to provide a sintering connection method for a rough copper surface processed by laser and nano-copper solder paste. By using laser processing to create micro-nano structures on the copper surface, the roughness of the copper surface is significantly increased. The copper surface is then sintered and connected with the nano-copper solder paste. This method can improve the shear strength of the copper interface by more than 50%.
[0005] To achieve the above objectives, the present invention provides a method for sintering a laser-processed rough copper surface to nano-copper solder paste, comprising the following steps: Step S1: A femtosecond laser with a wavelength of 1035 nm is used to perform laser micro-nano texturing on the copper substrate surface to be bonded; the laser pulse repetition frequency is set to 10 kHz, the laser output power is adjusted within the range of 200 mW-400 mW, and the laser scanning speed is controlled within the range of 500 μm / s-2000 μm / s; by matching the above laser process parameters, the surface of the copper substrate is subjected to micro-nano etching roughening treatment to obtain a roughened copper bonding base surface with a maximum surface contour height Rz of 30-60 μm; Step S2: Clean the roughened copper surface using an atmospheric pressure plasma cleaner with a discharge power of 150W-300W and a single-point treatment time of 60s-120s. Step S3: Apply the first layer of nano copper solder paste to the roughened copper surface after cleaning, let it stand and level, and then perform the first low-temperature drying at 150°C for 5 minutes. Step S4: After the first low-temperature drying, a second layer of nano-copper solder paste is coated on the surface. After standing and leveling, a second low-temperature drying is performed at a temperature of 100°C for 3 minutes to obtain a copper substrate with a coating layer. Step S5: Prepare two copper substrates with coatings, align and bond the coated surfaces of the two copper substrates together to form a sandwich bonding structure. Step S6: Apply pressure to the sandwich bonding structure and perform sintering at a higher temperature; Step S7: After sintering, cool to room temperature at a set cooling rate to obtain the sintered joint.
[0006] Furthermore, in step S1, an ultrafast laser is used to process micro-nano structures on the surface to be joined in order to control the roughness of the copper surface.
[0007] Furthermore, in steps S3 and S4, the nano-copper solder paste is coated using a screen printing process; and after each coating is completed, it is left to stand at room temperature for 5 minutes to allow the nano-copper solder paste to flow and level on the rough surface.
[0008] Furthermore, the first layer of nano-copper solder paste is used to fill the tiny depressions on the roughened copper surface; in step S4, the second layer of nano-copper solder paste is used to fill the gaps generated during the first coating and drying process.
[0009] Furthermore, in steps S3 and S4, the low-temperature drying process is as follows: heating to evaporate the organic components in the nano-copper solder paste, and then naturally cooling to room temperature after drying.
[0010] Furthermore, the room temperature was 25°C.
[0011] Furthermore, in step S6, a constant pressure of 0.2 MPa is applied to the surface of the upper substrate of the sandwich bonding structure for sintering.
[0012] Furthermore, in step S7, the cooling rate is set to 20℃ / min.
[0013] Furthermore, in step S5, the pretreatment process steps for the two copper substrates with coatings are completely identical.
[0014] Furthermore, in step S2, plasma cleaning is used to remove the oxide layer, oil, and impurities from the roughened copper surface.
[0015] The beneficial effects of this invention are as follows: This invention combines ultrafast laser micro / nano manufacturing technology with packaging and interconnect processes. Laser processing increases the roughness of the copper surface, enhancing the reliability of surface connections. A plasma cleaner removes contaminants from the copper surface. A first coating of nano-copper solder paste is applied to the copper surface, followed by evaporation of organic matter at 150°C for 5 minutes. A second coating is then applied, followed by evaporation of organic matter at 100°C for 3 minutes. These two copper surfaces are then joined to form a sandwich structure, which is then sintered at high temperature to form a reliable connection. This invention provides a sintering method applicable to rough copper surfaces by optimizing sintering process conditions and methods. Compared to existing technologies, the sintered body of this invention has a denser and more uniform interface, better shear strength, and a more stable and operable process, making it suitable for industrial mass production. Attached Figure Description
[0016] Figure 1 This is a flowchart of the invention; Figure 2 This is a schematic diagram illustrating the specific technical implementation process of the present invention; Figure 3 This is a schematic diagram of the equipment used for laser processing of copper surfaces. Figure 4 SEM images comparing solder filling before and after. Detailed Implementation
[0017] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0019] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0020] The following combination Figures 1-4 Specific embodiments of the present invention will be described in detail below. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the present invention.
[0021] This invention discloses a sintering bonding method for laser-processed rough copper surfaces and nano-copper solder paste, solving the technical problems of existing technologies such as difficulty in achieving reliable bonding on rough copper surfaces, the easy occurrence of defects such as voids and gaps at the sintered body interface, insufficient shear strength, poor process stability, high sintering temperature, high sintering pressure, and difficulty in adapting to industrial mass production. This invention provides a sintering bonding method for rough copper surfaces and nano-copper solder paste, offering a means and tool for research in the field of packaging interconnects, and meeting the practical needs of scientific research and industrial production.
[0022] like Figure 1 , Figure 2 As shown, a method for sintering a laser-processed rough copper surface with nano-copper solder paste includes the following steps: Step S1: Perform laser micro-nano processing on the surface of the copper substrate to be connected to obtain a roughened copper surface with a rough structure; Step S2: Perform plasma cleaning on the roughened copper surface; Step S3: Apply the first layer of nano copper solder paste to the roughened copper surface after cleaning, let it stand and level, and then perform the first low-temperature drying. Step S4: After the first low-temperature drying, a second layer of nano-copper solder paste is applied to the surface, and after standing and leveling, a second low-temperature drying is performed to obtain a copper substrate with a coating layer. Step S5: Prepare two copper substrates with coatings, align and bond the coated surfaces of the two copper substrates together to form a sandwich bonding structure. Step S6: Apply pressure to the sandwich bonding structure and perform sintering at a higher temperature; Step S7: After sintering, cool to room temperature at a set cooling rate to obtain the sintered joint.
[0023] The specific technical implementation process and steps are as follows: 1) Copper surface roughness: Select copper substrate A and copper substrate B of the same specifications, and use ultrafast laser to perform micro-nano processing on the surfaces of the two substrates to be joined. The processing method is as follows: Figure 3 As shown, precise roughening of the copper surface is achieved to obtain a rough surface with a preset roughness. A femtosecond laser with a wavelength of 1035nm is used to perform laser micro-nano texturing on the copper substrate surface to be bonded. The laser pulse repetition frequency is set to 10KHz, the laser output power is adjusted within the range of 200 mW-400mW, and the laser scanning speed is controlled within the range of 500μm / s-2000μm / s. By matching the above laser process parameters, the surface of the copper substrate is subjected to micro-nano etching roughening treatment to obtain a roughened copper bonding base surface with a maximum surface contour height Rz of 30-60μm. 2) Plasma cleaning: The roughened copper substrate A and copper substrate B are placed together in a plasma cleaner and plasma cleaning is performed using preset process parameters to remove the oxide layer, oil and impurities on the substrate surface and improve the activity of the copper surface; the roughened copper surface is cleaned using an atmospheric pressure plasma cleaner with a discharge power of 150W-300W and a single-point treatment time of 60s-120s. 3) First coating: On the rough surface of the copper substrate A after plasma cleaning, a layer of nano copper solder paste is uniformly coated using a screen printing machine. After coating, it is left to stand at room temperature for 5 minutes to ensure that the nano copper solder paste is fully leveled on the rough surface and fills the small depressions on the surface, thus obtaining nano copper solder paste-copper surface coating 1; wherein, the nano copper solder paste is composed of nano copper particles, ascorbic acid, benzimidazole and ethylene glycol, and the average particle size of the nano copper particles is 200nm; 4) First low-temperature drying: Place the nano copper solder paste-copper surface coating 1 in a drying device. Set the temperature of the first low-temperature drying to 100-150℃ and the duration to 3-5 minutes to evaporate the organic components in the nano copper solder paste. After drying, allow it to cool naturally to room temperature of 25℃ to obtain the dried coating A1. 5) Second coating: On the surface of the coated body A1 after low-temperature drying, a layer of nano copper solder paste is uniformly coated again using a screen printing machine. After coating, it is left to stand at room temperature for 5 minutes to ensure that the nano copper solder paste flows evenly and fills the tiny gaps that may have been generated during the first coating and drying process, thus obtaining nano copper solder paste-copper surface coating body 2. 6) Second drying: Place the nano copper solder paste-copper surface coating 2 in a drying device. Set the temperature of the second drying to 100-150℃ and the time to 1-3 minutes to evaporate the organic components in the nano copper solder paste in the second coating. After drying, allow it to cool naturally to room temperature of 25℃ to obtain the dried coating A2. 7) Pretreatment of copper substrate B: The process flow from step 1) to step 6) is completely applied to copper substrate B, which is roughened, plasma cleaned, coated twice and dried twice at low temperature to finally obtain dried coated body B2. 8) Lamination: Using the dried coating body A2 as the upper substrate and the dried coating body B2 as the lower substrate, the coating surfaces of the two substrates are precisely aligned and tightly bonded to ensure complete contact of the coating layers, forming a sandwich-style bonding structure. 9) Sintering: The bonding structure obtained in step 8) is placed in a sintering device, and a constant pressure of 0.1-0.5 MPa is applied to the surface of the upper substrate. Low-temperature sintering is carried out using a preset heating rate, sintering temperature and sintering time to cause the nano-copper solder paste to undergo a sintering reaction and form a dense sintered body. The sintering temperature is 200-300℃, the sintering pressure is 0.1-0.5 MPa, the sintering time is 30-60 min, the heating rate of both the upper and lower substrates is 15-20℃ / min, and the initial heating temperature is 25℃. 10) Cooling: The sintered body described in step 7 is cooled from the sintering temperature to room temperature (25°C) at a cooling rate of 20°C / min to avoid thermal stress caused by excessive cooling, which could lead to interface cracking, and finally to obtain a sintered bonded product with stable performance.
[0024] In this process, copper substrate A and copper substrate B are identical in their fabrication process, materials, and thickness. The side in contact with the nano-copper solder paste is roughened using laser processing. The main purpose of this roughening is to enhance the adhesion between the nano-copper paste and the copper surface. In step 1), the surfaces of copper substrate A and copper substrate B are roughened using laser processing to obtain a rough surface with an average roughness difference of 0.01-0.08 mm.
[0025] This invention is applicable to copper substrate interconnection processes in fields such as high-density integrated circuits, power devices, new energy vehicle electronics, and 5G communication equipment. It is especially suitable for electronic packaging scenarios that require high copper surface roughness, strict interconnection reliability, and large-scale mass production.
[0026] This invention solves the technical problems of existing technologies, such as difficulty in achieving reliable bonding on copper surfaces with large roughness, easy defects in the sintered body interface, insufficient shear strength, poor process stability, and difficulty in adapting to industrial mass production. The invention includes the following core steps: First, ultrafast laser is used to perform micro-nano processing on the surface of a copper substrate, precisely controlling the surface roughness to construct a rough interface with a high specific surface area; then, plasma cleaning technology is used to efficiently remove contaminants, oxide layers, and impurities from the copper surface, improving interface activity; next, through a two-coating-two-low-temperature drying process, nano-copper solder paste is layered and coated onto the copper surface, gradually evaporating the organic components in the solder paste and avoiding sintering defects caused by excessive thickness in a single coating; after performing the same pretreatment and coating process on two copper substrates, they are bonded together to form a "copper substrate-nano-copper solder paste-copper substrate" sandwich structure; finally, through precise temperature and pressure controlled high-temperature sintering and programmed cooling processes, a dense bond is achieved between the rough copper surface and the nano-copper solder paste, forming a reliable interconnect structure. This invention breaks through the limitations of traditional processes on copper surface roughness by systematically optimizing process parameters and innovating sintering methods. The resulting sintered body has a dense and uniform interface with excellent shear strength. Moreover, the entire process is stable, controllable, and highly operable, requiring no complex special equipment. It can adapt to the needs of large-scale industrial production and provides a new technical path for efficient interconnection of rough copper interfaces in the field of electronic packaging. It has significant engineering application value and industrial promotion prospects.
[0027] This invention addresses the problem of sintering connections on high-roughness copper surfaces. Existing methods suffer from complex processes, limited feasibility, long sintering times, high sintering temperatures, high sintering pressures, and limitations in mass production. This invention utilizes laser processing to fabricate micro / nano structures on the copper surface, significantly increasing surface roughness. A comparison of the sintering results between traditional methods and this invention demonstrates… Figure 4 As shown, the method of the present invention can improve the shear strength of the copper interface by more than 50%.
[0028] Figure 4 Left image: A femtosecond laser was used to process the surface of a copper substrate, forming microstructured copper arrays of 3mm×3mm×1mm and 8mm×8mm×1mm. Nano-copper solder paste was then uniformly coated onto these microstructured copper arrays using a syringe. The coated samples were then placed on a temperature-controlled digital heating stage, with two copper substrates stacked. The stage was heated to 300℃ at a rate of 20℃ / min and held for 30min. Finally, the temperature was lowered from the sintering temperature to room temperature (25℃) at a rate of 20℃ / min, yielding the desired result. Figure 4 The structure shown in the left image.
[0029] Figure 4The right figure shows that a femtosecond laser was used to process the surface of a copper substrate, forming microstructured copper arrays of 3mm×3mm×1mm and 8mm×8mm×1mm. Nano-copper solder paste was uniformly coated onto these microstructured copper arrays using a syringe. The coated samples were then placed on a temperature-controlled digital heating stage and heated to 50℃ at a rate of 20℃ / min and held for 3 min to allow for complete evaporation of anhydrous ethanol. Next, the temperature was increased to 160℃ at a rate of 20℃ / min and held for 5 min, followed by natural cooling. After cooling, nano-copper solder paste was uniformly coated again on the copper surface, and then the temperature was increased to 90℃ at a rate of 20℃ / min and held for 5 min. Finally, the two copper substrates were stacked, and the temperature was increased to 300℃ at a rate of 20℃ / min and held for 30 min. Finally, the temperature was decreased from the sintering temperature to room temperature (25℃) at a rate of 20℃ / min to obtain the desired result. Figure 4 The structure shown in the right figure.
[0030] In the description of this specification, references to terms such as "embodiment," "example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, those skilled in the art can combine or combine the different embodiments or examples described in this specification and the features therein without causing contradiction.
[0031] While embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions, and alterations to the above embodiments within the scope of the present invention.
Claims
1. A method for sintering a laser-processed rough copper surface with nano-copper solder paste, characterized in that, Includes the following steps: Step S1: Perform laser micro-nano processing on the surface of the copper substrate to be connected to obtain a roughened copper surface with a rough structure; Step S2: Perform plasma cleaning on the roughened copper surface; Step S3: Apply the first layer of nano copper solder paste to the roughened copper surface after cleaning, let it stand and level, and then perform the first low-temperature drying. Step S4: After the first low-temperature drying, a second layer of nano-copper solder paste is applied to the surface, and after standing and leveling, a second low-temperature drying is performed to obtain a copper substrate with a coating layer. Step S5: Prepare two copper substrates with coatings, align and bond the coated surfaces of the two copper substrates together to form a sandwich bonding structure. Step S6: Apply pressure to the sandwich bonding structure and perform sintering at a higher temperature; Step S7: After sintering, cool to room temperature at a set cooling rate to obtain the sintered joint.
2. The sintering connection method according to claim 1, characterized in that, In step S1, an ultrafast laser is used to process micro-nano structures on the surface to be joined in order to control the roughness of the copper surface.
3. The sintering joining method according to claim 1, characterized in that, In steps S3 and S4, the nano-copper solder paste is applied using a screen printing process; and after each application, it is left to stand at room temperature for 5 minutes to allow the nano-copper solder paste to flow and level on the rough surface.
4. The sintering joining method according to claim 1, characterized in that, In step S3, the first layer of nano-copper solder paste is used to fill the tiny depressions on the roughened copper surface; in step S4, the second layer of nano-copper solder paste is used to fill the gaps generated during the first coating and drying process.
5. The sintering joining method according to claim 1, characterized in that, In steps S3 and S4, the low-temperature drying process is as follows: heating to evaporate the organic components in the nano-copper solder paste, and then naturally cooling to room temperature after drying.
6. The sintering joining method according to claim 5, characterized in that, The room temperature is 25℃.
7. The sintering joining method according to claim 1, characterized in that, In step S6, a constant pressure of 0.2 MPa is applied to the surface of the upper substrate of the sandwich bonding structure for sintering.
8. The sintering joining method according to claim 1, characterized in that, In step S7, the cooling rate is set to 20℃ / min.
9. The sintering joining method according to any one of claims 1 to 8, characterized in that, In step S5, the pretreatment process steps for the two copper substrates with coatings are completely identical.
10. The sintering joining method according to claim 1, characterized in that, In step S2, plasma cleaning is used to remove the oxide layer, oil, and impurities from the roughened copper surface.
